Operational Effectiveness and Leverage on Profitability: The Moderating Role of Sales Growth in ASEAN Technology Companies - Reza Ananda Setya; Loggar Bhilawa (Universitas KH. Abdul Chalim Mojokerto, 2026)
The main objective of the research is to analyze how operational efficiency and leverage affect profitability with ASEAN technology companies in 2024, using sales growth as a moderating variable. This study utilizes secondary data, covering all technology companies in ASEAN listed in the Osiris database in 2024. The sample was determined using specific criteria, resulting in 87 samples from a population of 288. The research methodology employs a quantitative approach through statistical analysis using Moderated Regression Analysis (MRA). The findings of the study show that operational effectiveness has a positive impact on profitability, while leverage has an effect on profitability. Furthermore, sales growth does not moderate the effect of operational effectiveness and leverage on profitability. These findings identify that in increasing profitability, technology companies rely more on internal funding. Therefore, the more effectively a company utilizes its resources in carrying out operational activities, the greates its level of profitability will be.